The relationship between nurses’ caring behaviors and patient loyalty: trust towards nurses as a mediating role - Shima Sedighi; Amir Sadeghi; Ghodratollah Roshanaei; Zahra Purfarzad (BMC Nursing)
Abstract Background Most of the literature on factors influencing patient trust and loyalty has focused on measuring the quality of healthcare services, overlooking the role of nurses. To address this gap, the present study investigated the connection between nurses’ caring behaviors, patient trust in nurses, and patient loyalty. Also, the mediating role of trust towards nurses in relation between nurses’ caring behaviors with patient loyalty has been examined. Methods This study utilized a cross-sectional design and included a sample of 196 hospitalized patients from five universal hospitals in Iran. The participants were selected using stratified proportional random sampling based on the number of hospital beds and different departments. Data collection took place from October 2021 to April 2022. It involved gathering information on the patients’ demographic characteristics, as well as their responses to the Caring Behavior Inventory-24 (CBI-24), Trust in Nurses Scale (TNS), and a questionnaire on patient loyalty to the hospital. The collected data were analyzed using SPSS ver24 and AMOS ver24 software. Results The results indicate that patient perception of nurses’ caring behaviors has a significant and positive correlation with trust towards nurses and patient loyalty. Additionally, trust towards nurses also has a significant and positive correlation with patient loyalty. By controlling the demographic characteristics of the patients, there is an association between nurses’ caring behaviors with trust towards nurses (β = 0.756; R2 = 0.620; p < 0.001), nurses’ caring behaviors with patient loyalty (β = 0.565; R2 = 0.375; p < 0.001), and the trust toward nurse with patient loyalty (β = 0.602; R2 = 0.410; p < 0.001). The trust towards nurses was found to fully mediate the relationship between the nurses’ caring behaviors and patient loyalty (β = 0.503; p = 0.011; R2 = 0.48). Conclusions This study highlighted the crucial role of nursing care in fostering trust toward nurses, which in turn enhances patient loyalty. To promote a trusting relationship and increase patient loyalty, it is essential to improve nurses’ caring behaviors. Hospital administrators and nursing managers should focus on enhancing these behaviors in daily nursing practice.